Hagiographie et pandémie : analyse de la vie de Saint Roch - Llorca-Tonda, Maria Ángeles (L’art de vivre, de survivre, de revivre. Approches littéraires. Le 50e anniversaire des études romanes à l’Université de Łódź, 2022)
The Black Death that ravaged Europe in the second half of the 14th century inspiredmuch Middle Ages to think about explaining the trigger for the disease, but all accountscoincide on an underlying rationale: the divine anger falling on Men. The field ofart echoes the trauma caused by the pandemic to populations and the fear that leads toextreme behaviour (flagellants, dance of death, expiatory processions, etc.). Literature doesnot fail to stage the plague either, as evidenced by the Decameron, which in its first pagesdescribes the plague which is reaching the West through Italy. The hagiography, in turn,and specifically the genre of the Lives of Saints, becomes a significant source of informationon the description and repercussions of the disease in Europe. Thus, in this contribution wepropose to analyse La Vie et légende de monseigneur saint Roch, a French incunable of JehanPhelipot published in 1494, which went through three editions, in order to see how in thehagiographic text Roch’s ascent to holiness revolves around the theme of the plague diseaseand how the text becomes a source of information on the pandemic and its consequences.